Public-private partnership as a foundation of the financial stability of the state and households in the conditions of health care financing transformation in Ukraine - Kachula, Svitlana; Качула, Світлана Валентинівна; Lysiak, Liubov; Лисяк, Любов Валентинівна; Barannyk, Lilіia; Баранник, Лілія Борисівна; Masiuk, Iuliіa; Масюк, Юлія Володимиріна; Tereshchenko, Tetiana; Терещенко, Тетяна Євгенівна; Salnykova, Tetiana; Сальникова, Тетяна Валеріївна (Magnanimitas, 2023)
Among other mechanisms for maintaining the financial stability of state/local finances and household finances, the potential of public-private partnerships is significant. In this regard, the constructive interaction of the state and business in order to solve common financial, economic, and social problems is especially important. The article defines the role of public-private partnership in supporting the health care sector for providing the population with high-quality medical services and at the same time preserving the financial stability of the state and households; moreover, measures for its development are justified in the research. An assessment of the expenditures of the consolidated state budget for financing the industry, the degree of implementation of state programs and the results of self-assessment of the financial status of households for health care services in the conditions of the transformation of the mechanism of financing the industry and the Russian-Ukrainian war, under which the modern financial system of Ukraine functions, was carried out. The problems of implementation of the planned indicators of the state budget for the financing of the industry have been identified, which need to be solved. The advantages of public-private partnership for the state, private partners, and society are summarized. It is shown that the intensification of the process of implementation of projects/programs based on the principles of public-private partnership in the field of health care will ultimately contribute, other things being equal, to maintaining greater stability of household budgets and the state budget, increasing the efficiency of budget funds spending, as well as expanding the number of medical services and improving their quality. Measures for the development and support of public-private partnership are proposed, which will contribute to balancing the interests of the state, the private sector, and society to eliminate/solve problems in the field of health care under difficult conditions of war and the decline of economy, which will eventually become the basis for supporting the financial stability of the state/local budgets and finances of households and the private sector itself. Серед інших механізмів підтримання фінансової стійкості державних/місцевих фінансів та фінансів домогосподарств вагомим є потенціал державно-приватного партнерства. У зв'язку з цим конструктивна взаємодія держави та бізнесу з метою вирішення спільних фінансово-економічних та соціальних проблем особливо важлива. У статті визначається роль державно-приватного партнерства у підтримці сфери охорони здоров’я для забезпечення населення якісними медичними послугами і водночас збереження фінансової стійкості держави та домогосподарств, а також обґрунтовуються заходи щодо його розвитку. Проведено оцінку видатків зведеного, державного бюджету на фінансування галузі, ступінь виконання державних програм та результатів самооцінювання фінансового стану домогосподарств на послуги у сфері охорони здоров’я в умовах трансформації механізму фінансування галузі та російсько-української війни, за яких функціонує сучасна фінансова система України. Виявлено проблеми реалізації запланованих показників державного бюджету на фінансування галузі, що потребують вирішення. Узагальнено переваги державно-приватного партнерства для держави, приватних партнерів і суспільства. Показано, що активізація процесу реалізації проєктів/програм на засадах державно-приватного партнерства у сфері охорони здоров’я у підсумку сприятиме за інших рівних умов дотриманню більшої стійкості бюджетів домогосподарств та державного бюджету, підвищенню ефективності витрачання бюджетних коштів та розширення кількості і покращення якості медичних послуг. Запропоновано заходи щодо розвитку та підтримки державно-приватного партнерства, що сприятимуть збалансуванню інтересів держави, приватного сектора та суспільства для усунення/вирішення проблем в галузі охорони здоров’я в складних умовах війни та падіння економіки, що у підсумку стане підґрунтям підтримки фінансової стійкості державного/місцевих бюджетів та фінансів домогосподарств і самого приватного сектора.
Державно-приватне партнерство як підґрунтя фінансової стійкості держави та домогосподарств в умовах трансформації фінансування охорони здоров’я в Україні
Keywords: public-private partnership; державно-приватне партнерство; budget; бюджет; health care; охорона здоров’я; financing; фінансування; household expenses; витрати домогосподарства; financial capacity; фінансова спроможність; financial sustainability; фінансова стійкість